Interproximal reduction versus lower incisor extraction - Cabezas Choque, Eddy Edwin (2022)
Dental crowding is present in a large percentage of the population. The amount of crowding increases with age and is one of the most common problems in dental practice, especially in the field of orthodontics. Two principal ways to resolve the lower anterior crowding are dental extractions and enamel interproximal reduction. The objective of the present study was to perform a literature review on the effects of applying the enamel interproximal reduction technique in comparison with the lower incisor extraction method for correcting the lower anterior crowding. This literature review involved the analysis of 34 articles published (either in Spanish or English) between 2004 and 2020 from SciELO, PubMed and Google Scholar databases. The most relevant results were the following: the interproximal reduction and the lower incisor extractions are effective in the treatment of class I malocclusions with permanent dentition that present moderate lower anterior crowding. However, more evidence supporting that this is the best treatment option is needed. In conclusion, clinical intervention is an individual-based decision that must consider crowding, dental and oral health, dental characteristics, patient expectations, and the use of articulated models.